2003
DOI: 10.1016/s0735-1097(03)00924-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced myocardial perfusion reserve and transmural perfusiongradient in heart transplant arteriopathyassessed by magnetic resonance imaging

Abstract: Magnetic resonance perfusion imaging detects Tx-CHD by a decreased MPR. After exclusion of LV hypertrophy and prior rejection, resting Endo/Epi ratio alone might be sufficient to indicate Tx-CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 21 publications
3
65
0
3
Order By: Relevance
“…Although to the best of our knowledge the present study is the first on CFR by CE-TTE, CFR has been previously studied in HT patients by other methods (3,(12)(13)(14)(15)(16).…”
Section: Cfr In Ht: Ce-tte Versus Other Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although to the best of our knowledge the present study is the first on CFR by CE-TTE, CFR has been previously studied in HT patients by other methods (3,(12)(13)(14)(15)(16).…”
Section: Cfr In Ht: Ce-tte Versus Other Methodsmentioning
confidence: 97%
“…The discrepancy may relate to: small sample size and/or very few patients with CAV (13,15), selection bias due to technical difficulty in performing the invasive measurements in severe CAV (14), various definitions of CAV by angiography (13,14) and/or by IVUS (14,15). In addition, noninvasive studies, which failed to show a correlation between the reduced CFR and CAV, used positron emission tomography (15) or MRPI (13), therefore they are not comparable with CE-TTE.…”
Section: Cfr In Ht: Ce-tte Versus Other Methodsmentioning
confidence: 99%
“…Unfortunately, microvascular disease in this study could not be assessed. They also demonstrated that patients with CAV have a reduced myocardial perfusion even during rest conditions [114] . In regards to CMR tissue characterization, Steen et al [115] showed that more than 80% of patients with severe angiographic CAV had a late gadolinium enhancement pattern suggesting subendocardial infarction with a distribution consistent with the angiographic pattern.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 95%
“…The use of adenosine for myocardium stress perfusion after heart transplantation has not been widely reported. Nevertheless, Muehling et al [114] showed a reduced myocardial perfusion reserve in patients with CAV with good correlation between MRI and invasive measurements. Unfortunately, microvascular disease in this study could not be assessed.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Magnetic resonance coronary angiography, at present, shows limited sensitivity for detecting CAV and positron emission tomography (PET) has not yet been well studied (Muehling et al, 2003).…”
Section: Ivus Parameters Include Intimal Thickness Intimal Index Anmentioning
confidence: 99%